Generalized allometry for the estimation of total aerial biomass of woody plants: Theoretical general framework and its applications - Paz Pellat, Fernando; Velázquez Rodríguez, Alma; Sánchez Sánchez, Cristóbal; Salas Aguilar, Víctor; Méndez González, Jorge; Acosta Mireles, Miguel; Nájera Luna, Juan Abel (Instituto de Ecología, A.C., 2021)
Estimates of total aerial biomass and carbon are important in relation to carbon markets and forest productivity, so it is important to develop cost-effective methods that reduce the uncertainty in the estimates. The use of allometric equations between total aerial biomass, and trunk or total volume, and normal diameter and total height is common practice in forest inventories, with the use of specific and generalized models, with different levels of uncertainty. In the literature, various methodologies have been proposed to simplify the use of allometric relationships, with some proposals with correct bases, but without exploring their implications and understanding the associated mathematics. In this paper a general theoretical framework of the relations between the exponents and constants and, between exponents of the allometric equations is presented, using as a base simple mathematics. The theoretical framework is applied to a base of parameters of allometric relationships and a set of data bases of field measurements, resulting in estimations comparable to the classic allometric equations, but only with the use of the relationship between total height and normal diameter. The theoretical proposal is explored in its consequences, generating recommendations for a paradigm shift in the allometric developments for woody plants.